2017
DOI: 10.1038/srep45217
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of superconductivity and charge-density wave in the quasi-one-dimensional material HfTe3

Abstract: We present the first experimental evidence for metallicity, superconductivity (SC) and the co-existence of charge density waves (CDW) in the quasi-one-dimensional material HfTe3. The existence of such phenomena is a typical characteristic of the transition metal chalcogenides however, without the application of hydrostatic pressure/chemical doping, it is rare for a material to exhibit the co-existence of both states. Materials such as HfTe3 can therefore provide us with a unique insight into the relationship b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…A spin density wave is a spin‐density modulation and is caused by eletron‐hole pairing or singularities in the magnetic susceptibility . CDWs or SDWs were observed in many superconductors, for example Pb and Nb, HfTe 3 or NbSe 2 , and the coexistence or competition between these electronic phases is debated. Another closely related phenomena is the phonon drag effect that was recently found in undoped CoSi .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A spin density wave is a spin‐density modulation and is caused by eletron‐hole pairing or singularities in the magnetic susceptibility . CDWs or SDWs were observed in many superconductors, for example Pb and Nb, HfTe 3 or NbSe 2 , and the coexistence or competition between these electronic phases is debated. Another closely related phenomena is the phonon drag effect that was recently found in undoped CoSi .…”
Section: Resultsmentioning
confidence: 99%
“…[21] The interference of the electrons with phonons lead to local binding of the free electrons and thus changes the conduction electron density of states. [23] CDWs or SDWs were observed in many superconductors, [23] for example Pb and Nb, [24] HfTe 3 [25] or NbSe 2 , [26] and the coexistence or competition between these electronic phases is debated. A CDW is connected to a structural distortion in the crystal lattice.…”
Section: Formation Of a Potential Cdw Phase Evidenced In The Temperatmentioning
confidence: 99%
“…, respectively. In high-T c oxides and other known CDW superconductors, the observed superconducting critical temperatures are lower than their dielectric counterparts: T c < T s [6,7,9,11,24,[156][157][158][159].…”
Section: Hamiltonian and Order Parametersmentioning
confidence: 96%
“…1(a), it has a layered structure stacked along the c-direction. In each layer, 1-D chains along the b-direction spread in alignment along the a-direction [10,14,15]. Previous diffraction studies found a periodic lattice distortion in ZrTe3 [16][17][18][19][20].…”
mentioning
confidence: 93%